2019
DOI: 10.3892/mmr.2019.10009
|View full text |Cite
|
Sign up to set email alerts
|

Construction and dissection of the ceRNA‑ceRNA network reveals critical modules in depression

Abstract: The prevalence of mental health disorders such as depression is high. Depression is a multifactorial disorder and its underlying mechanisms remain unclear. Competing endogenous RNA (ceRNA) regulation has been reported to serve important roles in human disease. In the present study, ceRNA networks for depression and the corresponding normal physiological states were constructed. Further analysis of the ceRNA networks revealed that ceRNA regulation may be important for depression. Hub ceRNAs including high mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Growing evidence indicates that the ceRNA regulation mechanism plays a role in disease progression and drug efficiency [137][138][139][140]. We checked if any of the DE lncRNAs in the infected cells were exerting such effects to ensure a particular miRNA does not downregulate a gene.…”
Section: Discussionmentioning
confidence: 99%
“…Growing evidence indicates that the ceRNA regulation mechanism plays a role in disease progression and drug efficiency [137][138][139][140]. We checked if any of the DE lncRNAs in the infected cells were exerting such effects to ensure a particular miRNA does not downregulate a gene.…”
Section: Discussionmentioning
confidence: 99%
“…Over the last few years, numerous studies have validated the ceRNA theory. It is well known that disruption of the balance of ceRNA cross-talk is associated with various developmental processes and pathological conditions, including tumorigenesis, neurodegenerative diseases (e.g., Alzheimer’s disease (AD)) 23 , and mental disorders (e.g., SCZ and depression) 24 , 25 .…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated the activity of ceRNA regulatory loops and the related networks in several pathological conditions and developmental processes, e.g., tumorigenesis, neurodegenerative diseases 38 , and mental disorders 39 , 40 . There may be various ceRNAs, including mRNAs, pseudogenes, circRNAs, and lncRNAs, in a network 31 .…”
Section: Discussionmentioning
confidence: 99%